Kaantabay sa Kauswagan Mass Housing Strategy: The Case of Naga City - Anicia C. Sayos (Philippine Institute for Development Studies (PIDS), 1998)
With the passage of Local Government Code in 1991, LGUs are challenged to efficiently manage its resources given the responsibility of delivering of basic services. With this premise, the "Population and Urbanization: Managing the Urbanization Process Under a Decentralized Governance Framework ", a joint project of National Economic and Development Authority, Philippine Institute for Development Studies and Development Academy of the Philippines, has attempted to look at the means and strategies of some LGUs in handling the problems caused by rapid urbanization in fiscal/environmental management, health and housing sectors. This paper highlights the strategies adapted by Naga City in implementing its award-winning Kaantabay sa Kauswagan housing program for the urban poor.
Keywords: 330; governance; housing program; fiscal management; urbanization